2016
DOI: 10.1111/ijfs.13079
|View full text |Cite
|
Sign up to set email alerts
|

Development of rice as potential carriers for probiotic Lactobacillus amylovorus

Abstract: An experiment using a standard strain of Lactobacillus amylovorus TISTR1110 to test for the capability of carbohydrate utilisation of nine cultivars of rice found that L. amylovorus TISTR1110 could utilise carbohydrate from all cultivars and also exhibit nonhaemolytic properties. After testing the viability of the strain under simulated gastrointestinal tract conditions by enumeration after 5 h, the results showed that the amount of L. amylovorus TISTR1110 present was 4.0 9 10 5 CFU/mL or a 73.78% survival rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…The gut microbiota have physiological functions associated with immune system and maintenance of intestinal homeostasis. A recent study showed that LP rice had a high survival rate of probiotic bacteria compared with other Thai rice cultivars [26] and black rice also had prebiotic activity in regulating the intestinal environment [27]. Thus, the current authors are now evaluating the effects of LP extract on the changing of microbiota in guts of IBD in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota have physiological functions associated with immune system and maintenance of intestinal homeostasis. A recent study showed that LP rice had a high survival rate of probiotic bacteria compared with other Thai rice cultivars [26] and black rice also had prebiotic activity in regulating the intestinal environment [27]. Thus, the current authors are now evaluating the effects of LP extract on the changing of microbiota in guts of IBD in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to test the affinity of this same strain collection to other food components in future work, in order to dispose of more comparison points to our study and to get a better understanding of the importance of adhesion to β-lactoglobulin compared to adhesion to other food components. Currently, the rare existing studies discussing bacterial adhesion to food components other than β-lactoglobulin concern up to four strains at most at a time (De Bellis et al, 2010; Chumphon et al, 2016; Tarazanova et al, 2017, 2018a,b; Utratna et al, 2017), therefore failing to provide an overview of adhesion to food components amongst wide bacterial groups such as the LAB group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact and technological interest of adhesive interactions is yet poorly documented and largely remains to be investigated (Hickey et al, 2015). Adhesive interactions between bacterial surface components and dairy components have only been studied for very few wild type strains, namely LGG (Guerin et al, 2016), Lactobacillus amylovorus (Chumphon et al, 2016), and Lactobacillus paracasei (De Bellis et al, 2010). This article goes one step forward in that direction by applying the high-throughput screening method recently developed by Gomand et al (2018) to a collection of 73 LAB strains (for which genome sequence is available) in order to characterize their potential adhesive behavior toward the major dairy protein β-lactoglobulin, to which the adhesive behavior of the model strain LGG is already well-known (Burgain et al, 2013b, 2014b, 2015; Guerin et al, 2016, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Most probiotic products are developed using Lactobacillus, Bifidobacterium, Bacillus such as Enterococcus and Weisella. At present, there is one strain of yeast (Saccharomyces boulardii) used as a probiotic (Chumphon et al, 2016;Azad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa) is a principal food for more than one-half the world's population (Chumphon et al, 2016). In particular, many varieties of Thai-pigmented rice have been developed in many countries including Thailand where they are recognised for their nourishing phytochemical content, such as cultivar glutinous Luem Pua, Black Jasmine and Riceberry rice (Thipart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%